TECHNOLOGICAL COMPETITION AMONG THE ARCTIC COUNTRIES WITH THE CONSIDERATION OF CHALLENGES AND THREATS OF ARCTIC EXPLORATION (ON THE BASIS OF THE EU CORPORATIVE LEVEL) - N. N. Bondareva (Модернизация, инновация, развитие, 2018)
Purpose: the purpose of the research is to study the current state of technological competition between the leading Arctic States, its impact on the Russian Federation, as well as to develop recommendations for Russia to take into account the future direction of relevant global and regional trends. Methods: the presented research was carried out on the basis of the ecosystem approach and comparative analysis of open sources, using the generally accepted theoretical methods of scientific knowledge.Results: the article defines the most significant European participants of the technological competition in the Arctic region (the Russian Federation, Norway, Sweden, Denmark, etc.) on the level of governments and corporations. The main objectives, tasks, plans, projects and scale of state and company technological competition in the Arctic is defined. The analysis of the importance of valuable international methodological experience of country technological capacity-building in the Arctic is carried out. The forecast is given to the forthcoming repartition of spheres of influence in the Arctic, the reasons of transformation of the global market taking into account nearest future market supply of new volumes of minerals from the European Arctic are shown. The analysis of historical and modern activity of Arctic participants, resources supply, new markets and their influence on the Russian Federation is carried out. Recommendations about consideration by the Russian Federation of future world and regional technological and other trends are offered.conclusions and Relevance: the analysis of the state of technological competition between the Arctic countries, as well as future plans for the development of the Arctic from their side, proves the forecast of active search of complex benefits from environmental changes in the Arctic. Considering the rapid change in the global environment at the transnational level, the growing technological vulnerability and isolation of Russia, it is necessary for the Russian Federation to take timely into account new opening trends in the development of the Arctic. In this sense, it is very important to maintain the pace of the Russian Federation's increasing its technological competence in the Arctic.